ATF6 enables pathogen infection in ticks by inducing stomatin and altering cholesterol dynamics - Kaylee A. Vosbigian; Sarah J. Wright; Brianna P. Steiert; Kristin L. Rosche; Elis A. Fisk; Elisabeth Ramirez-Zepp; Jason M. Park; Eric A. Shelden; Dana K. Shaw (Proceedings of the National Academy of Sciences, 2025)
How tick-borne pathogens interact with their hosts has been primarily studied in vertebrates where disease is observed. Comparatively less is known about pathogen interactions within the tick. Here, we report that Ixodes scapularis ticks infected with either Anaplasma phagocytophilum (causative agent of anaplasmosis) or Borrelia burgdorferi (causative agent of Lyme disease) show activation of the ATF6 branch of the unfolded protein response (UPR). Disabling ATF6 functionally restricts pathogen survival in ticks. When stimulated, ATF6 functions as a transcription factor, but is the least understood out of the three UPR pathways. To interrogate the Ixodes ATF6 transcriptional network, we developed a custom R script to query tick promoter sequences. This revealed stomatin as a potential gene target, which has roles in lipid homeostasis and vesical transport. Ixodes stomatin was experimentally validated as a bona fide ATF6-regulated gene through luciferase reporter assays, pharmacological activators, RNA interference transcriptional repression, and immunofluorescence microscopy. Silencing stomatin decreased A. phagocytophilum colonization in Ixodes and disrupted cholesterol dynamics in tick cells. Furthermore, blocking stomatin restricted cholesterol availability to the bacterium, thereby inhibiting growth and survival. Taken together, we have identified the Ixodes ATF6 pathway as a contributor to vector competence through Stomatin-regulated cholesterol homeostasis. Moreover, our custom, web-based transcription factor binding site search tool “ArthroQuest” revealed that the ATF6-regulated nature of stomatin is unique to blood-feeding arthropods. Collectively, these findings highlight the importance of studying fundamental processes in nonmodel organisms.